Women’s Religious Journeys and Muslim Identity Reconstruction: A Phenomenological Study of Converts in Medan, Indonesia - Muhammad Zaki Arrafi; Muhammad Jailani (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
Religious conversion is not completed through the formal adoption of a new religious affiliation but develops through religious learning, social negotiation, and identity reconstruction. This study examines how women affiliated with Mualaf Center Kampung Madras in Medan interpret their religious journeys and how social interactions contribute to the formation of their identities as Muslim women. The study employed a qualitative phenomenological design involving five women converts aged 31–60 as primary participants and the head of Mualaf Center Kampung Madras as a supporting key informant. Data were collected through semi-structured interviews, nonparticipant observation, and documentation. The data were analyzed through bracketing, intuiting, analyzing, and describing, while symbolic interactionism was used to interpret the construction of religious meaning and identity. The findings identified four interrelated themes: diverse pathways to conversion, post-conversion challenges and religious adjustment, social support and the role of the Mualaf Center, and the reconstruction of the self as a Muslim woman. Conversion was shaped by marriage, spiritual attraction, and prolonged interaction with Muslim social environments. After conversion, participants encountered limited religious knowledge, negative family responses, emotional pressure, and socioeconomic difficulties. Support from spouses, neighbors, religious teachers, Muslim communities, and the Mualaf Center facilitated religious learning and reduced social isolation. The findings demonstrate that Muslim identity was constructed gradually through the interpretation of religious symbols, interaction with significant others, and negotiation between personal agency and socially internalized expectations. The study highlights the importance of sustained, non-coercive, and context-sensitive support for women converts.